Credit relevance after mandatory IFRS adoption in deposit money banks of Nigeria - Dagwom Yohanna Dang; James Ayuba Akwe; Salisu Balago Garba (Emerald Publishing Limited, 2020)
Credit relevance of financial reporting can be influenced by change in financial reporting framework. This study aims to examine the effect of mandatory international financial reporting standards (IFRS) adoption on credit relevance quality of financial reporting of deposit money banks (DMBs) in Nigeria.This study uses difference-in-differences (D-in-D) design for its modelling. Panel data regression analysis based on the D-in-D model is used in analysing the data collected from secondary sources.The findings of this study are that based on the D-in-D approach, there is a significant and positive effect of mandatory IFRS adoption on credit relevance quality of financial reporting of DMBs in Nigeria, and that there is also a significant difference in the credit relevance quality of financial reporting of mandatory adopting banks in the post-mandatory IFRS adoption period compared to pre-mandatory IFRS adoption period.To the best of this study's review, there is inadequacy of literature within the credit relevance research in Nigeria. In the light of this, this study intends to fill the gap.This study is specifically important to regulatory authorities, both primary and secondary regulators. Specifically, this study has implications in the regulatory roles of Central Bank of Nigeria (CBN) and Financial Reporting Council of Nigeria (FRC). However, the study recommends that regulatory authorities should encourage DMBs to avail their financial reports annually to credit rating agencies (local and international) for proper evaluation for subsequent ratings.The peculiarities in this study, that is the utilisation of the D-in-D design and the use of credit relevance metric as the dependent variable, made this study important and novel to push the frontier of existing knowledge.